Flavor tagged time-dependent angular analysis of the Bs→J/ψϕ decay and extraction of ΔΓs and the weak phase ϕs in ATLAS - Aad, G. (2014)
A measurement of the Bs0→J/ψϕ decay parameters, updated to include flavor tagging is reported using 4.9  fb-1 of integrated luminosity collected by the ATLAS detector from s=7  TeV pp collisions recorded in 2011 at the LHC. The values measured for the physical parameters are ϕs=0.12±0.25(stat)±0.05(syst)  radΔΓs=0.053±0.021(stat)±0.010(syst)  ps-1Γs=0.677±0.007(stat)±0.004(syst)  ps-1|A∥(0)|2=0.220±0.008(stat)±0.009(syst)|A0(0)|2=0.529±0.006(stat)±0.012(syst)δ⊥=3.89±0.47(stat)±0.11(syst)  radwhere the parameter ΔΓs is constrained to be positive. The S-wave contribution was measured and found to be compatible with zero. Results for ϕs and ΔΓs are also presented as 68% and 95% likelihood contours, which show agreement with the Standard Model expectations.